STEAM learning through yapılandırmacı yaklaşım (constructivist approach): A descriptive study in Turkey elementary schools - Rahman, Delfi Ikhlasiah; Yusmaliana, Desfa (EduStream: Jurnal Pendidikan Dasar, 2025)
This study aims to describe the implementation of the constructivist approach (Yapılandırmacı Yaklaşım) in STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning in Turkey elementary schools. The study used descriptive qualitative method, involving an in-depth, semi-structured interview with one primary school teacher in Antalya. Data were collected through a literature study and the interview and analyzed using the Miles and Huberman interactive model of analysis. To support the data management, coding, and theme categorization process, NVivo software was utilized, which helped in systematically visualizing the relationships between themes. The findings of this study show that the constructivist approach has been formally adopted in the Turkey national curriculum since 2004 and supports student-centered learning. However, its implementation is not always consistent due to problems such as the characteristics of the subject matter, time limitations, and variations in teacher readiness. Furthermore, STEAM learning is not yet widely known or implemented in state elementary schools, whereas private schools is more well prepared in terms of facilities and curricular flexibility. The result of NVivo visualization clarifies that the integration of STEAM and constructivism is theoretically highly relevant for improving student engagement, creativity, and problem-solving, but at the implementation level, it still requires strengthening teacher capacity, educational policy support, and reforms in teacher education curricula. Therefore, the study concludes that the success of constructivism- based STEAM learning is highly dependent on systemic readiness, which encompasses teacher training, policy support, and the provision of adequate facilities.